Confined optical-phonon-assisted cyclotron resonance in quantum wells via two-photon absorption process. (June 2016) - Phuc, Huynh Vinh; Hien, Nguyen Dinh; Dinh, Le; Phong, Tran Cong
Abstract: The effect of confined phonons on the phonon-assisted cyclotron resonance (PACR) via both one and two photon absorption processes in a quantum well is theoretically studied. We consider cases when electrons are scattered by confined optical phonons described by the Fuchs-Kliewer slab, Ridley's guided, and Huang-Zhu models. The analytical expression of the magneto-optical absorption coefficient (MOAC) is obtained by relating it to the transition probability for the absorption of photons. It predicts resonant peaks caused by transitions between Landau levels and electric subband accompanied by confined phonons emission in the absorption spectrum. The MOAC and the full-width at half-maximum (FWHM) for the intra- and inter-subband transitions are given as functions of the magnetic field, temperature, and quantum well width. In narrow quantum wells, the phonon confinement becomes more important and should be taken into account in studying FWHM. Highlights: Nonlinear two-photon absorption in quantum well has been studied via investigating the PACR. The result is limited by the combined interaction of three confined phonon models. The MOAC and FWHM depend significantly on magnetic field, temperature and well width. The influence of phonon confinement is very important at a narrow quantum well.